Strategi Guru Pendidikan Agama Islam dalam Meningkatkan Motivasi Belajar Siswa di UPT SPF SD Inpres Perumnas L Makassar - Nuwayyar Azizah Azzah; Sulaeman Sulaeman; Ahmad Nashir (Jurnal Budi Pekerti Agama Islam, 2025)
This study aims to determine (1) the types of strategies used by Islamic Religious Education teachers to enhance students' learning motivation at UPT SPF SD Inpres Perumnas I Makassar, (2) the impact of implementing these strategies on students' learning motivation at UPT SPF SD Inpres Perumnas I Makassar, and (3) the supporting and inhibiting factors influencing Islamic Religious Education teachers in enhancing students' learning motivation at UPT SPF SD Inpres Perumnas I Makassar. This research employs a qualitative descriptive approach to gather factual information and truths occurring in the field through data collection techniques such as observation, interviews, and documentation. The findings of this study indicate that (1) Islamic Religious Education teachers use various strategies to enhance students' learning motivation, including expository, contextual learning, cooperative learning, inquiry, ice-breaking activities, reinforcement, praise, punishment, and grading. (2) The implementation of these strategies has positively impacted students' motivation by increasing enthusiasm for learning, improving focus, fostering responsibility for both academic and non-academic tasks, and preventing boredom during the learning process. (3) The supporting factors in the teaching and learning process include adequate facilities and infrastructure, as well as the application of effective and efficient teaching methods. Meanwhile, the inhibiting factors faced by students include a lack of parental awareness in providing attention and support for their education, as well as the influence of peers who tend to be less motivated in participating in learning activities.